A Pre-Caching Strategy Based on the Content Relevance of Smart Device’s Request in Information-Centric IoT - Moli Zhang; Bowei Hao; Ruilin Wang; Ye Wang (IEEE Access, 2020)
In recent years, investigations on various forms of solution for Internet of Things (IoT) paradigm opens the new era of smart devices. The Information-Centric Internet of Things (IC-IoT) can apply the characteristics of content caching which is a typical feature of Information-Centric Networking. Therefore, designing an efficient caching strategy for IC-IoT is able to improve the efficiency of smart devices. In this paper, we propose a Pre-Caching Strategy based on the Relevance of smart device request Content, namely PCSRC. After the first request of content chunk at a smart device side, PCSRC pre-caches the rest of the content chunks. There are two types of cached content chunks, that is, actual requested content chunks and pre-caching content chunks. Actual requested content chunks are pushed forward hop-by-hop according to the trend of the local activity. The popular content will be gradually pushed to the edge of IC-IoT. Furthermore, a sojourn time of a cached content chunk is employed to save storage space. The simulation results show PCSRC can reach 42.7% on the cache hit ratio with the different storage sizes. For the average hop count, PCSRC can increase about 42.2% than that of ProbCache. And PCSRC can improve about 47.9% than that of CEE for the average hop count.